One-Kind Hybrid Power Means of the Two-Term Exponential Sums and Quartic Gauss Sums - Xiaoxue Li; Li Chen (Journal of Mathematics)
The main purpose of this article is using the analytic methods and the properties of the classical Gauss sums to study the calculating problem of the hybrid power mean of the two-term exponential sums and quartic Gauss sums and then prove two interesting linear recurrence formulas. As applications, some asymptotic formulas are obtained.